Behavior of PPE Use Among Employees at PT. X (Oil and Gas Sector) - Hariyono, Anelka Bugihadinata (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to explore the behavior of employees at PT. X regarding the use of personal protective equipment (PPE) and identify barriers and support factors for PPE implementation. Methods: A qualitative study using a case study approach was conducted, with participants selected through purposive sampling. In-depth interviews were carried out with employees of PT. X, and data were analyzed using inductive analysis techniques. Results: The participants were male employees of PT. X. The in-depth interviews revealed that the compliance level of PT. X employees in using PPE is still low. Barriers to PPE implementation at PT. X include low self-awareness among employees and some PPE being unfit for use. Support for PPE implementation at PT. X includes company regulations that align with the Ministry of Manpower's guidelines, such as the establishment of Standard Operating Procedures (SOPs) and regular inspections within PT. X. Conclusion: The implementation of PPE use among employees at PT. X is considered inadequate, and the enforcement of existing regulations needs improvement. Strategies to enhance employee compliance with PPE use at PT. X include: 1) Increasing employee awareness about the importance of PPE through safety work socialization and Occupational Health and Safety (OHS) training, 2) Imposing sanctions and implementing an incentive system, 3) Replacing damaged PPE with new equipment, 4) Enhancing coordination among employees, and 5) Utilizing technology, such as an Indoor Positioning System, to monitor PPE use.